2007
DOI: 10.1051/0004-6361:20078252
|View full text |Cite
|
Sign up to set email alerts
|

A photometric study of Be stars located in the seismology fields of COROT

Abstract: Context. In preparation for the COROT mission, an exhaustive photometric study of Be stars located in the seismology fields of the mission has been performed. The very precise and long-time-spanned photometric observations gathered by the COROT satellite will give important clues on the origin of the Be phenomenon. Aims. The aim of this work is to find short-period variable Be stars located in the seismology fields of COROT, and to study and characterise their pulsational properties. Methods. Light curves obta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…Projected rotational velocities of 430 km s −1 (Gutiérrez‐Soto et al 2007) and 500 km s −1 (Aragona et al 2010) have been reported for MWC 148, whereas 262 ± 26 km s −1 (Yudin 2001) and 300 ± 50 km s −1 (Williams et al 2010) for MWC 656. We decided to estimate the rotational broadening v sin i from our own spectra following the technique outlined in Marsh, Robinson & Wood (1994), which basically subtracts broadened templates from the average spectrum of the target and searches for the lowest residual.…”
Section: Description Of the Spectra And Rotational Broadeningmentioning
confidence: 90%
“…Projected rotational velocities of 430 km s −1 (Gutiérrez‐Soto et al 2007) and 500 km s −1 (Aragona et al 2010) have been reported for MWC 148, whereas 262 ± 26 km s −1 (Yudin 2001) and 300 ± 50 km s −1 (Williams et al 2010) for MWC 656. We decided to estimate the rotational broadening v sin i from our own spectra following the technique outlined in Marsh, Robinson & Wood (1994), which basically subtracts broadened templates from the average spectrum of the target and searches for the lowest residual.…”
Section: Description Of the Spectra And Rotational Broadeningmentioning
confidence: 90%
“…The star is known to exhibit light variability on several timescales and to undergo outbursts. Gutiérrez-Soto et al (2007) investigated the variability of HD 49330 using data acquired by a 4-year campaign at the Observatorio de Sierra Nevada (OSN) and large datasets provided by the Hipparcos mission and the All Sky Automated Survey (ASAS-3) (Pojmanski 2002 The light curve of ASAS-3 ( Fig. 1) shows a quasi-cyclical variation of about 1600 days, and includes events of shorter duration.…”
Section: Hd 49330: Parameters and Known Variabilitymentioning
confidence: 99%
“…Observations were carried out one year prior to the LRA1 run of CoRoT to investigate spectroscopically the rapid variability previously detected in photometry by Gutiérrez-Soto et al (2007). Seventy spectra with high spectral resolution and high signal-to-noise ratio were obtained.…”
Section: Ground-based Observationsmentioning
confidence: 99%